2018
DOI: 10.1002/2017ef000641
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic Market‐Driven Regional Shifts of Cropping Practices Reduce Food Production Capacity of China

Abstract: China is facing the challenge of feeding a growing population with the declining cropland and increasing shortage of water resources under the changing climate. This study identified that the opportunistic profit‐driven shifts of planting areas and crop species composition have strongly reduced the food production capacity of China. First, the regional cultivation patterns of major crops in China have substantially shifted during the past five decades. Southeast and South China, the regions with abundant water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…Note that it has been suggested that the potential spring irrigation in India would advect more water vapor to southern China [ 56 ]; L in could thus increase more over Southeast China, and the combined increase in spring water vapor would be advected further to Southeast Asia and to the Pacific. Although not considered in our model, irrigation expansion (expansion of the area irrigated and, in some regions, the amount of irrigation water applied) has been reported over cropping areas in Northwest, North and Northeast China over the past decades [ 57 ]; this also may contribute to spring LE enhancement, for example, as well as increasing water vapor content in northern China.…”
Section: Discussionmentioning
confidence: 99%
“…Note that it has been suggested that the potential spring irrigation in India would advect more water vapor to southern China [ 56 ]; L in could thus increase more over Southeast China, and the combined increase in spring water vapor would be advected further to Southeast Asia and to the Pacific. Although not considered in our model, irrigation expansion (expansion of the area irrigated and, in some regions, the amount of irrigation water applied) has been reported over cropping areas in Northwest, North and Northeast China over the past decades [ 57 ]; this also may contribute to spring LE enhancement, for example, as well as increasing water vapor content in northern China.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, urbanization may also have influenced cropping systems by increasing/decreasing winter wheat planting areas at the expense of other crop types. As urbanization can lead to a shift in cropping systems, for instance, increasingly more farmers plant market-driven crop species to optimize the household income [45]. Hence, in such circumstances, the winter wheat planting areas can be sustained and show an increasing tendency (3.32(±0.25) × 10 7 ha) characterized even by a significant increase in some provinces (Hebei and Shandong).…”
Section: Dynamics Of Winter Wheatmentioning
confidence: 99%
“…On the one hand, China has maintained agricultural self-sufficiency in grains in most years, even though agriculture needs to compete for scarce land resources with urbanization and industrialization [23], and has lifted 700 million people out of poverty. On the other hand, with economic development, population growth, and diet changes, the challenges China is facing in balancing food supply and demand have increased significantly [24,25]. Diet structures have changed dramatically from plant-based to oil and livestock foods in the last 30 years, and so more agricultural resources have been required.…”
Section: The Chinese Contextmentioning
confidence: 99%